Distribution of regional lymph nodes metastasis in 870 cases of nasopharyngeal carcinoma and the suggestions for individualized elective prophylactic neck irradiation with intensity‐modulated radiotherapy - Lei Wang; Zheng Wu; Qian He; Yiting Li; Subin Wang; Feiping Li; Hui Wang; Wenhui Li; Yaqian Han (Cancer Medicine, 2024)
Abstract Purpose To explore the feasibility of individualized elective prophylactic neck irradiation (iEPNI) for optimizing current approach by investigating metastatic lymph nodes (LNs) distribution in nasopharyngeal carcinoma (NPC). Materials and Methods Records of 870 NPC patients without distant metastasis in Hunan Cancer Hospital from January 2019 to December 2019 were reviewed. LNs' locations were identified based on the 2013 guidelines. The intra‐regional lymphatic drainage (IRLD) areas included Station 1st (level VIIa and II), Station 2nd (level III and Va), and Station 3rd (level IV, Vb, and Vc). Other levels were categorized as extra‐regional areas. Results Among the 870 patients, 94.5% cases exhibited LNs metastasis, including unilateral metastasis in 198 patients and bilateral metastasis in 624 patients. In the whole cohort, the most common involved IRLD areas were level IIb (87.1%), VIIa (80.0%), IIa (61.8%), Va (30.6%), IV (21.4%), Vb (8.9%), and Vc (1.1%). Besides, rates of LNs metastasis in Station 1st, 2nd, and 3rd were 94.3%, 61.1%, and 22.9%, respectively. Only four patients (4, 0.5%) revealed skipping metastasis among the three stations. Conclusions Lymph node metastasis follows an organized pattern from Station 1st to 3rd with scarce skipping metastasis. A potential iEPNI strategy of prophylactic neck irradiation to the ipsilateral latter node‐negative station appears promising in NPC patients. Further prospective investigations are warranted to validate the approach.